Analysis of The Need for Green Open Space (RTH) as an Absorptor of Carbondioxide Gas Emissions in The Semarang-Yogyakarta National Road Corridor, Bergas District, Semarang Regency - Kusuma, Andika Satya Widyatama; Rudiarto, Iwan; Mussadun, Mussadun (Eduvest - Journal of Universal Studies, 2023)
Semarang Regency is one of the areas in Central Java Province which has a variety of complex environmental problems, one of which is increasing carbon dioxide gas (CO2) emissions and the limited availability of green open space, especially in the Bergas District area. The increase in CO2 gas emissions is due to the increasing trend of the population in Bergas District and this is directly proportional to the increasing number of ownership of motorized vehicle transportation. This study aims to examine the need for Green Open Space based on the ability of vegetation to absorb carbon dioxide (CO2) on the Semarang-Yogyakarta National Corridor Road, Bergas District, Semarang Regency, Central Java Province. Data collection in this study was carried out by traffic counting to calculate CO2 emissions and field observations to calculate the absorption capacity of CO2 emissions by vegetation. The results of this study indicate that the emissions produced by vehicles passing through the Semarang - Yogyakarta National Road corridor in Bawen District are 4,108,137.18 gr/hour, and emissions that can be absorbed by vegetation are only 642,846.47 gr/hour. So that the remaining emissions that have not been absorbed are 3,465,290.71 gr/hour. In order to optimally absorb the remaining emissions, at least 370 Swietenia mahagoni, 436 Pterocarpus indicus, 358 Samanea saman and 432 Bauhinia purpurea are needed.